Kommunikativnye cennosti v zerkale media: "zaduševnostʹ” vs. “svetskostʹ” vs. “glamurnostʺ” v sovrem - Dementʹev, Vadim V. (Stylistyka, 2010)
In the article, Russian communicative values have been discussed. Such values belong to the best clues for understanding a national culture. The media speech material is an effective tool for researching the communicative values. The contexts with the lexical names of three Russian communicative values and tncir parts have been selected out of the contemporary Russian newspapers with an aid of the Integrum system, and then the counotative meaning of these contexts have been analyzed.